Qualitative assessment of individuals at a family health center: avoidance/refusal of COVID-19 vaccination: - SiL, Ertan; Mazıcıoğlu, Mümtaz; Nahya, Nilüfer; Bilgici, Ethem (General Practice, 2024)
Background. The avoidance or refusal of vaccines is a significantpublic health problem during the COVID-19 pandemic.This article focuses on vaccine avoidance and refusal amongpatients at a Family Health Center (FHC). We will attempt toidentify and describe the factors that contribute to avoidance andrefusal so that new strategies can be developed.Methods. This study was conducted between December2021 and August 2022. Eight individuals were interviewed witha semi-structured form. The study cite was Turgut Reis FHCKayseri/Turkey. Thematic analysis was used to analyze the qualitativedata.Results. The study identified three main themes and 16sub-themes based on verbatim notes. The main themes were thelevel of knowledge regarding COVID-19 and individual andnon-individual factors causing COVID-19 vaccine avoidance/refusal.Some of the sub-themes included the reality of the disease,protective measures, concerns about the content and productionprocess of the vaccine, the interaction between chronic diseaseand COVID-19, and the positive or negative effects of religionand national identity on vaccination. The study demonstratedthat concerns about vaccine safety, efficacy, and production, aswell as individual preferences, media influence, and mandatoryregulations of health care management were the most influentialfactors in vaccine avoidance/refusal.Conclusions. The sudden onset of COVID-19 resulted in adelayed response from society and health authorities. This delaymay be due to distrust of the disease, reluctance to adopt preventivemeasures, and uncertainty about treatment options. Whileadvanced technology exists, limited public information about thevaccine’s effectiveness and production processes could be contributingto this reaction.
Keywords: COVID-19; Vaccination refusal; prevention